Reformation of Islamic Education in Indonesia - Salafudin Salafudin (STABN RADEN WIJAYA WONOGIRI, 2022)
This study examines the Islamic education system, which continues to be an exciting discussion among education practitioners. This is a form of public concern and concern for the current objective condition of Islamic educational institutions, especially in Indonesia. This is library research, namely research sourced from library materials using a qualitative approach. In this case, the researcher explored several primary and secondary data with the following steps: reading and studying in-depth primary data such as books, journals, articles, theses, theses, and dissertations related to the discussion of Islamic education reform in Indonesia. The results of this study reveal that the long journey of Islamic education has provided various forms of Islamic education models in Indonesia. In this case, Islamic education also participates in the renewal of the education system in Indonesia. So, it can be said that Islamic education in Indonesia has a significant impact in terms of the turmoil of renewal and changes in the direction of education in Indonesia, both in the ideological and practical realms. Thus, the long journey of Islamic education in Indonesia is a manifestation of the reform of Islamic education and is the driving force and determinant of the direction of reforming Islamic education in Indonesia. So, it can be concluded that the reform of Islamic education in Indonesia can show how dynamic the journey of Islamic education in Indonesia is. This can be seen from the many different models of Islamic education that exist in the world of education in Indonesia.